Report of the Working Group on Equipment and Scientific Instruments for Educational Institutions - Planning Commission (Planning Commission, 1967)
The Planning Commission set up a Working Group in 1965 to examine the position of scientific equipment and instruments required for various educational institutions up to the end of the Fifth Plan. The Group was also to review the present indigenous capacity for manufacturing these equipments as well as the requirements and procedures of import of essential equipment. The Working Group broke up into a number of committees to consider the requirements of scientific equipment and instruments in schools, universities and colleges, engineering and technological institutions, medical institutions and agricultural colleges and universities.
Government of India Planning Commission
Government of India Planning Commission